Peran Agama dalam Demokrasi dari Perspektif Fukuyama dan Kontekstualisasinya bagi Politik di Indonesia - Ario Tejo Sugiarto, Bernardus (Fakultas Teologi, Universitas Sanata Dharma, 2025)
Religion and democracy are frequently opposed in terms of the power legitimacy system. The basis of power legitimacy from religious perspective comes from above or from God Himself, while the basis of power legitimacy from democratic perspective comes from below or from the people. Religion uses reasoning of faith or belief, while democracy uses rational reasoning. Fukuyama contends that the liberal democratic system is the most appropriate system of power legitimacy for a modern secular society. In the context of Indonesian politics, religion and democracy cannot be separated simply because the people involved in democracy are people who believe in God and are religious as well. Indonesian society is a religious society that uses a democratic system to legitimize power. The experience of religion has been integrated into all aspects of Indonesian life including social and political life. However, religion has never been the basis for governing the country. In this study, the researcher specifically investigates the role of religion in the democratic process from Fukuyama's perspective. The research issues are: 1) what is the contribution of religion in the practice of democracy, 2) what are the limits of religious involvement in the practice of democracy, 3) how is its contextualization in the practice of democracy in Indonesia which has its own characteristics in religious plurality. This research is a literature study of Fukuyama works from 1992 to 2018 which discusses the dynamics of state and religious relations. The purpose of the study is to provide a critical assessment of the role of religion in the practice of democracy in Indonesia from the Fukuyama perspective. Religion is a symbol of the presence of The Transcendent. With the presence of religion, humans are still reminded that there is a higher power than worldly power so that humans are not arbitrary in exercising their political power. Therefore, religion must maintain its position outside the practice of democracy. When religion is involved practically in political power, religion will be placed under human power and used as a means of legitimacy of power.AbstrakAgama dan demokrasi sering dipertentangkan dalam hal sistem legitimasi kekuasaan. Dasar legitimasi kekuasaan dari perspektif agama berasal dari atas atau dari Tuhan sendiri, sedangkan dasar legitimasi kekuasaan dari perspektif demokrasi berasal dari bawah atau dari rakyat. Agama menggunakan penalaran iman atau keyakinan, sedangkan demokrasi menggunakan penalaran yang bersifat rasional. Fukuyama berpendapat bahwa sistem demokrasi liberal merupakan sistem legitimasi kekuasaan yang paling sesuai dengan masyarakat modern yang sekular. Dalam konteks politik Indonesia, agama dan demokrasi tidak dapat dipisahkan begitu saja karena rakyat yang terlibat di dalam demokrasi adalah manusia-manusia yang ber-Tuhan dan beragama. Masyarakat Indonesia merupakan masyarakat religius yang menggunakan sistem demokrasi untuk melegitimasi kekuasaan. Penghayatan agama sudah menyatu ke dalam semua aspek kehidupan bangsa Indonesia termasuk kehidupan sosial dan politik. Namun demikian, agama tidak pernah menjadi dasar untuk mengatur negara. Dalam penelitian ini, peneliti secara khusus menyelidiki peran agama di dalam proses demokrasi dari perspektif Fukuyama. Persoalan-persoalan penelitian adalah: 1) apakah sumbangan agama dalam praktik demokrasi, 2) apakah batasan keterlibatan agama dalam praktik demokrasi, 3) bagaimana kontekstualisasinya dalam praktik demokrasi di Indonesia yang mempunyai kekhasan dalam pluralitas agama. Penelitian ini merupakan studi literatur terhadap karya-karya Fukuyama dari tahun 1992 sampai dengan 2018 yang membahas dinamika hubungan negara dan agama. Tujuan penelitian adalah memberikan penilaian kritis terhadap peran agama dalam praktik demokrasi di Indonesia dari perspektif Fukuyama. Agama simbol kehadiran Sang Transenden. Dengan hadirnya agama, manusia tetap diingatkan bahwa ada kekuasaan yang lebih tinggi daripada kekuasaan duniawi sehingga manusia tidak semena-mena dalam menjalankan kekuasaannya. Oleh karena itu, agama harus mempertahankan posisinya di luar demokrasi. Ketika agama terlibat di dalam kekuasaan politik secara praktis, maka agama akan diletakkan di bawah kekuasaan manusia dan digunakan sebagai sekadar alat legitimasi kekuasaan.